2013
DOI: 10.1021/cb3007314
|View full text |Cite
|
Sign up to set email alerts
|

A Biocompatible in Vivo Ligation Reaction and Its Application for Noninvasive Bioluminescent Imaging of Protease Activity in Living Mice

Abstract: The discovery of biocompatible reactions has had a tremendous impact on chemical biology, allowing the study of numerous biological processes directly in complex systems. However, despite the fact that multiple biocompatible reactions have been developed in the past decade, very few work well in living mice. Here we report that D-cysteine and 2-cyanobenzothiazoles can selectively react with each other in vivo to generate a luciferin substrate for firefly luciferase. The success of this “split luciferin” ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 118 publications
(438 reference statements)
1
57
0
1
Order By: Relevance
“…Moreover, impressive advances in luciferase engineering and ease of targeting by genetic encoding permit the broad use of such reporters for in vivo imaging with cell and tissue specificity (41,43,44). We and others have developed caged luciferins, which are enzymeinert luciferin derivatives that are chemically unmasked to the luciferin substrate in the presence of an analyte or biochemical event of interest for subsequent enzymatic generation of light (45)(46)(47)(48)(49)(50); in particular, our laboratory has used this approach to develop bioluminescent H 2 O 2 reporters (45,47). To create a Cu + -responsive luciferin probe, we exploited a Cu + -dependent oxidative cleavage reaction mediated by the tetradentate ligand TPA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, impressive advances in luciferase engineering and ease of targeting by genetic encoding permit the broad use of such reporters for in vivo imaging with cell and tissue specificity (41,43,44). We and others have developed caged luciferins, which are enzymeinert luciferin derivatives that are chemically unmasked to the luciferin substrate in the presence of an analyte or biochemical event of interest for subsequent enzymatic generation of light (45)(46)(47)(48)(49)(50); in particular, our laboratory has used this approach to develop bioluminescent H 2 O 2 reporters (45,47). To create a Cu + -responsive luciferin probe, we exploited a Cu + -dependent oxidative cleavage reaction mediated by the tetradentate ligand TPA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Work from our laboratory and others has demonstrated the utility of caged luciferins in vivo (28)(29)(30) for measuring transient small molecules (31)(32)(33)(34), enzyme and transporter activities (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), protein-protein and cell-cell interactions (42,47,48), and copper (49). Indeed, previous work from our laboratory utilized a Cu-dependent oxidation reaction to uncage luciferin for in vivo copper imaging (50), a first demonstration of a general activitybased sensing (ABS) strategy which we envisioned expanding to other essential metals in biology by changing the reaction trigger.…”
mentioning
confidence: 99%
“…We previously reported that D-cysteine and 2-cyanobenzothiazole (CBT) can selectively react with each other in vivo to generate luciferin substrates for firefly luciferase (“split luciferin reaction”, Fig. 1) (Godinat et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…We previously reported application of this “split luciferin reaction” for the real-time and non-invasive imaging of apoptosis, associated with activation of caspase 3/7 (Godinat et al, 2013). Caspase-dependent release of free D-cysteine from the caspase 3/7-specific peptidic substrate Asp-Glu-Val-Asp-D-Cys (DEVD-(D-Cys)) allowed further reaction with 6-amino-2-cyanobenzothiazole (NH 2 -CBT) in vivo and subsequent formation of 6-amino-D-luciferin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation